KKN-Thematic: Building A Tourism Village and Creative Economy In-Person Tutoring in Cijeruk Village, Dayeuhluhur District, Cilacap Regency. - Ai Nurhayati; Arni Sri Wahyuni; Dea Sopia; Deni Maulana; Hasbi Assidqi; Irma Silvi Fauziah; Lisma Septiani; Neng Dewi Noor F; Siti Desi Nazila; Wahda Robiatul A; Yuda Lugiana; Budi Hendrawan (Jurnal Ksatria : Jurnal Pengabdian Kepada Masyarakat, 2024)
The offline tutoring activities in Cijeruk Village, Cilacap District, were carried out as part of the KKN-T UMTAS community service program targeting elementary school students residing in Cijeruk Village. The activities aim to (1) assist students in understanding materials they have not yet grasped, (2) help students complete assigned tasks so they do not experience difficulties, and (3) also to participate in reducing COVID-19 clusters in the education sector. The offline tutoring also results in elementary school students better understanding the material provided and becoming more helpful in completing school assignments.